The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.1007/978-3-540-73214-3_15
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Uncertainty and Reasoning

Abstract: Abstract. This article gathers and consolidates the issues involved in uncertainty relating to reasoning and analyzes how uncertainty visualizations can support cognitive and meta-cognitive processes. Uncertainty in data is paralleled by uncertainty in reasoning processes, and while uncertainty in data is starting to get some of the visualization research attention it deserves, the uncertainty in the reasoning process is thus far often overlooked. While concurring with the importance of incorporating data unce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
0
50
1
Order By: Relevance
“…We expect it may be of value to integrate this or the interpreter's confidence directly into the visualization as a decision aid. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We expect it may be of value to integrate this or the interpreter's confidence directly into the visualization as a decision aid. 26 …”
Section: Resultsmentioning
confidence: 99%
“…26 MacEachren proposed the use of colour saturation and blurring as being conducive to indicate uncertainty. 13 These attributes may intuitively be more natural encodings but their superiority to other encodings remains to be proven.…”
Section: Uncertainty Visualizationmentioning
confidence: 99%
“…There are many general categorisations of uncertainty in the literature: Gershon [18] discusses a taxonomy of imperfection; Thomson et al [54] present a typology of uncertainty for geospatially referenced information for intelligence analysts; Skeels et al [46] derive a classification from commonalities in uncertainty areas uncovered through qualitative interviews; and Zuk and Carpendale [59] extend Thomson's typology to support reasoning uncertainty. In our workshop session described in section 4, we identified three specific types of uncertainty as being of interest to our DAs in their HTA.…”
Section: Storing Uncertaintymentioning
confidence: 99%
“…Research has shown that factors such as personality [18,53], spatial ability [9], biases [29,54,55] and emotional state [3,17,23,34,41,45] impact a user's performance. Though progress is undeniable, a common limitation is that every cognitive factor that affects visualization performance is not considered or properly controlled.…”
Section: Introductionmentioning
confidence: 99%